Intra-cyclic velocity variation of the center of mass and hip in breaststroke swimming with maximal intensity - Gourgoulis, V.; Koulexidis, S.; Gketzenis, P.; Tzouras, G. (The Journal of Strength and Conditioning Research, 2018)
The aim of the study was to compare the center of mass (CM) and hip (HIP) intracyclic velocity variation in breaststroke swimming using 3-dimensional kinematic analysis. Nine male breaststrokes, of moderate performance level, swam 25-m breaststroke with maximal intensity, and their movements were recorded, both under and above the water surface, using 8 digital cameras. Their CM and HIP velocities and their intracyclic variations were estimated after manual digitization of 28 selected points on the body in a complete arm and leg breaststroke cycle. Paired sample t-tests or Wilcoxon tests, when the assumption of normality was broken, were used for statistical analyses. In both, CM and HIP velocity-time curves, the results revealed a similar pattern of 2 clear peaks associated with the leg and arm propulsive phases and 2 minimal velocities that corresponded to the arm and leg recovery phase and the lag time between the leg and arm propulsive phases, respectively. However, despite this similar general pattern, the HIP minimum resultant velocity was significantly lower, whereas its maximal value was significantly greater, than the corresponding CM values. Consequently, the HIP intracyclic swimming velocity fluctuation significantly overestimates the actual variation of the swimmer's velocity in breaststroke swimming.